1976
DOI: 10.1017/s002211207600236x
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional turbulence above topography

Abstract: Using a one-layer quasi-geostrophic model, we study the effect of random monoscale topography on forced beta-plane turbulence. The forcing is a uniform steady wind stress that produces both a uniform large-scale zonal flow U (t) and smaller-scale macroturbulence characterized by both standing and transient eddies. The large-scale flow U is retarded by a combination of Ekman drag and the domain-averaged topographic form stress produced by the eddies. The topographic form stress typically balances most of the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
203
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(222 citation statements)
references
References 5 publications
19
203
0
Order By: Relevance
“…[6] In the absence of direct external forcing, eddy fluxes tend to reduce large scale potential vorticity gradients, therefore driving anticyclonic flow above topographic bumps [Bretherton and Haidvogel, 1976]. One expects then that time-mean of the eddy term h eddy is positive (resp.…”
Section: Basic Mechanismmentioning
confidence: 99%
“…[6] In the absence of direct external forcing, eddy fluxes tend to reduce large scale potential vorticity gradients, therefore driving anticyclonic flow above topographic bumps [Bretherton and Haidvogel, 1976]. One expects then that time-mean of the eddy term h eddy is positive (resp.…”
Section: Basic Mechanismmentioning
confidence: 99%
“…Quite another approach was taken by BRETHERTON and HAIDVOGEL (1976) who observed that quasi two-dimensional flows dissipate enstrophy preferentially over energy. The tendency thus is towards a state of minimum enstrophy for given energy.…”
Section: Process Models In Eddy Dynamicsmentioning
confidence: 99%
“…For a given energy there are in general multiple stationary solutions of (15) for di erent v alues of . Yet only the steady-states that lie on the branch > ; 1 are nonlinearly stable and thus are the most physically relevant moreover, they minimize the potential enstrophy for given energy ( 19]). Carnevale and Frederiksen 18] show that in the limit of in nite resolution the canonical equilibrium is statistically sharp and identical to the nonlinearly stable minimum enstrophy state.…”
Section: Energy-enstrophy Theoriesmentioning
confidence: 99%
“…The emergence of such states as averages over large time intervals in damped and driven numerical simulations has been studied extensively with many interesting results ( 1,19,20,21,22]). Here, in a complementary direction, we devise and test crude closure algorithms based on the energy-enstrophy statistical theory where the entire closure is based on a single predicted evolving parameter, the energy.…”
mentioning
confidence: 99%